Determinants of Students’ Achievement in Senior Secondary School Mathematics in South-Western Nigeria (2014)
Students‘ under-achievement in Mathematics over the years in South-western, Nigeria has been partially attributed to ineffective school management and poor classroom interaction. Studies on Secondary School Mathematics achievement have so far concentrated on teacher-student related factors with less emphasis on the combination of principals‘ leadership styles, Teachers‘ job satisfaction and classroom management. This study investigated the causal relationship among principal factors, teachers‘ job satisfaction and classroom management, and students‘ achievement in Mathematics in South-western, Nigeria. The study adopted a survey design with a hypothesised model. Two states (Oyo and Ogun) were randomly selected. Proportional sampling technique was used to select thirty Local Government Areas (LGAs) from the two states, while the simple random sampling technique was used to select five schools from each LGA; making a total of 150. In all, participants were 162 SS2 Mathematics teachers and 5,251 SS2 students. Principals‘ Supervisory Role Rating Scale (r = 0.70, CVR = 0.73); Teachers‘ Job Satisfaction Rating Scale (r = 0.76, CVR = 0.72), Teachers‘ Classroom Management Scale (r = 0.80, CVR = 0.71), Mathematics Achievement Test (r = 0.74, CVR = 0.69) and Multifactor Leadership Scale with four components( r = 0.70, CVR = 0.78) were used to collect data. Data were analysed using multiple regression and path analysis at p≤0.05. The hypothesised and parsimonious model explained factors influencing Mathematics achievement with six discrepancies occuring out of the 59 cases which is just 10.2%. The model was predicted by all the independent variables at forty-two point two percent. One hundred and five pathways were established with 29 direct and 76 indirect. Out of the 11 variables influencing Mathematics achievement, 5 variables (Transformational; β=0.523, Democratic; β=0.291, Teacher job satisfaction; β=0.199, Laissez-faire; β=0.183 and Teacher classroom management; β=0.177) had direct effect on Mathematics achievement. Apart from principals‘ supervisory role, principals‘gender, age, qualification, experience and autocratic leadership style had indirect effect on Mathematics achievement. Transformational leadership style had the most significant effect on Mathematics achievement (0.562), followed by democratic leadership style (-0.274), teacher‘s job satisfaction (0.270), laissez-faire leadership style (-0.190), classroom management (0.177), principals‘ gender (0.088), principasl‘ qualification (0.087), principals‘ age (0.082), autocratic leadership style (0.021) and principals‘ experience (0.008). Principal‘s leadership styles and socio-demographic factors significantly influenced teachers job satisfaction, classroom management and ultimately, students‘ achievement in senior secondary schools in Oyo and Ogun states respectively. Principals should therefore be cautious in their leadership styles towards inproving teachers‘ job satisfaction, classroom management and students‘ achievement generally in their schools